Presenting a structural model of the relationship between defense styles in cluster B personality disorders and the mediating role of emotional cognitive regulation - Tababaeipour, Badrosadat; Khosropour, Farshid; Zenoozian, Saeedeh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was conducted with the aim of presenting a structural model of the relationship between defense styles in cluster B personality disorders and the mediating role of emotional cognitive regulation. Methods: The research method is cross-sectional correlation. The statistical population of this study consisted of all male and female students of Tehran Azad University in 1399, from which 395 people were selected by multi-stage cluster sampling. In this study, Millon clinical multivariate tools, cognitive emotion regulation (Garnowski and Craig, 2006), defense styles (Anders et al., 1993) were used, all of which had acceptable validity and reliability. Structural equation modeling was used to answer the research hypotheses. Results: Findings showed that the model has a good fit. The results also showed that the developed defensive styles had a significant direct negative effect on b-cluster personality disorders. Developed defense styles have a direct positive effect on cognitive regulation of positive emotion and a direct negative effect on cognitive regulation of negative emotion. Cognitive regulation of positive emotion has a direct negative effect on personality disorders of cluster b. Cognitive regulation of negative emotion also had a direct positive effect on personality disorders of cluster b. Developed defense styles have had an indirect effect on cluster b personality disorders by regulating positive and negative emotions. Conclusion: Therefore, paying attention to the mentioned variables in prevention and designing more appropriate treatments helps researchers and therapists.